The Genesis of «thesaurus»concept in the theory of education management - Kozlova, O. G. (Problems of Engineer-Pedagogical Education, 2018)
The essence of the notion "thesaurus" is revealed in the article, the results of the terminological analysis of scientific literature on the transformation of the thesaurus concepts in the theory of education management are presented. The study allowed identifying three directions of the thesaurus of the domestic theory of education management development: borrowing foreign concepts; justification for separate concepts management and conceptual systems solving specific management problems; appearance of the first works in which an attempt to provide the thesaurus of the theory of education management as a whole systems phenomenon is made. It was determined that the evolution of lexicography form of the thesaurus has led to the emergence of many of its species, a comprehensive description which can give a detailed classification. It is proved that: the problem of the terminological device is very complicated, which can be solved on the basis of system-integrated approach; development of a conceptual and terminological apparatus in education promotes deeper awareness of the essence of the phenomenon, and, consequently, more effective management of any system of this kind.